2013
DOI: 10.5897/ajb2013.12154
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of fungal endophytes and their bioactive metabolites from endemic plants of Tirumala hills-Seshachalam biosphere reserve

Abstract: This study investigates the endophytic fungal diversity of three endemic plants of Tirumala hills also their capabilities for the production of hydrolysing enzymes and secondary metabolites. Our study provides the first evidence on the diversity, enzyme and metabolite charecterisation of fungal endophytes from the untapped endemic plants of Tirumala Hills of Seshachalam Biosphere Reserve, Easternghats, Andhra Pradesh, India. A total of 13 endophytic fungi isolates were obtained and grouped into seven genera ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…This result is superior to those of Sunitha et al (2013) and Panuthai et al (2012), where, among the fungal isolates obtained, only a few could produce laccase. It was reported that most laccase producers are wood rooting fungi and are responsible for the removal of toxic phenols (Pragathi et al, 2013). This property may confer the endophyte with antioxidant properties, which characterize extracts of these fungal isolates when measured quantitatively.…”
Section: Resultsmentioning
confidence: 99%
“…This result is superior to those of Sunitha et al (2013) and Panuthai et al (2012), where, among the fungal isolates obtained, only a few could produce laccase. It was reported that most laccase producers are wood rooting fungi and are responsible for the removal of toxic phenols (Pragathi et al, 2013). This property may confer the endophyte with antioxidant properties, which characterize extracts of these fungal isolates when measured quantitatively.…”
Section: Resultsmentioning
confidence: 99%
“…There is still inadequate information about interaction between dipterocarp trees and fungal endophytes. Study of endophyte in dipterocarp tree was done by Orachaipunlap et al (2008) and Pragathi et al (2013), but this study focuses on foliar endophyte.…”
Section: Introductionmentioning
confidence: 99%